Behavior and Immune Response of Conventional and Slow-Growing Broilers to Salmonella Typhimurium - Snyder, Ashlyn M.; Riley, Sean P.; Robison, Cara I.; Karcher, Darrin M.; Wickware, Carmen L.; Johnson, Timothy A.; Weimer, Shawna L. (Frontiers in Physiology, 2022)
Fast growth rate in broiler chickens comes with welfare concerns and the contribution of growth rate to pathogen resistance and sickness behavior is relatively unknown. The objective of this study was to evaluate physiological and behavioral responses of conventional (CONV) and slow-growing (SG) male broilers challenged with Salmonella Typhimurium. CONV (N=156) and SG (N=156) chicks were raised in a pen with wood litter shavings until day 7 of age, when birds were transferred to 24 isolators (N=11 chicks/isolator). On day 14 of age, half of the birds (N=12 isolators) were challenged with S. Typhimurium (ST) and the other half (N=12 isolators) received a control (C). On days 7, 13, 17, 21, and 24, body weight was recorded, and blood, jejunum and ileum sections were collected from 2 birds/isolator (N=48 birds/sampling) to measure plasma IgA and IgG and intestinal histomorphology, respectively. On days 12, 16, 21, and 23, video was recorded to evaluate bird postures (sitting, standing, or locomoting) and behaviors (eating, drinking, preening, stretching, sham foraging, allopreening, and aggression). CONV birds were 70 g heavier (P=0.03) on day 21 and 140 g heavier (P=0.007) on day 24 than SG. On day 7, CONV jejunum villus height and crypt depth were 22 μm and 7 μm greater (P≤0.001), respectively, than SG. On day 24, ST ileum villus height was 95 μm shorter (P=0.009) than C. IgA increased after day 17 for all birds and at day 21, CONV IgA was greater (P=0.01) than SG. Although SG IgG was 344 μg/mL greater (P=0.05) than CONV on day 7, CONV IgG increased with age (P<0.0001) to greater (P≤0.03) concentrations than SG on day 21 and day 24 by 689 μg/mL and 1,474 μg/mL, respectively, while SG IgG remained at similar concentrations after day 13. Generally, a greater proportion of birds sham foraged as they aged (P<0.0001). A greater proportion of CONV tended to sit (P=0.09) and fewer locomoted (P<0.0001) than SG as they aged. The results illustrate conventional and slow-growing broilers differ in their behavior, immunity, and response to Salmonella.